2005
DOI: 10.1007/s00221-004-2157-x
|View full text |Cite
|
Sign up to set email alerts
|

Grip forces when passing an object to a partner

Abstract: The goal of the present study was to investigate how grip forces are applied when transferring stable control of an object from one person to another. We asked how grip forces would be modified by the passer to (1) control for inertial forces as the object was transported toward the receiver and (2) control for the impending perturbation when the receiver made contact with the object. Twelve volunteers worked in pairs during this experiment. One partner, playing the role of passer, transported an object with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 27 publications
5
82
0
1
Order By: Relevance
“…We found that the passer began releasing their grasp before the receiver completed the acquisition (see Figure 3[h]). This degree of precision and tight synchronization between two strangers has been previously documented as well (Mason & C. L. MacKenzie, 2005). It is also worth noting that despite the limited visual cues and high accuracy and precision demands of this passing task, through the 1,080 trials performed in this experiment, not a single block was dropped.…”
Section: Temporal Coordination Between Passer and Receiversupporting
confidence: 76%
See 1 more Smart Citation
“…We found that the passer began releasing their grasp before the receiver completed the acquisition (see Figure 3[h]). This degree of precision and tight synchronization between two strangers has been previously documented as well (Mason & C. L. MacKenzie, 2005). It is also worth noting that despite the limited visual cues and high accuracy and precision demands of this passing task, through the 1,080 trials performed in this experiment, not a single block was dropped.…”
Section: Temporal Coordination Between Passer and Receiversupporting
confidence: 76%
“…Huber et al (2008) also demonstrated the first pattern described by Shibata, with the passer arriving first and assuming a near stationary state. Finally, Mason and C. L. MacKenzie (2005) studied the object-transfer phase of passing tasks by measuring grip forces. They found varying patterns of force production by pairs at object contact.…”
Section: Acquisition Of Moving and Passed Targets In Natural Environmmentioning
confidence: 99%
“…Different aspects of hand-overs between humans have been studied in the literature. This includes grip forced applied by humans during hand-overs [14], trajectories and velocity profiles adopted by humans both in the role of giver and receiver [16], and the social modification of the instrumental movement of pick-and-place in the context of hand-overs [3]. While these studies have interesting implications on humanrobot hand-overs, there is not much evidence suggesting that approaches that will work best for human-robot hand-overs are the ones adopted during human-human hand-overs.…”
Section: Introductionmentioning
confidence: 99%
“…We also observed passing prehension [33] when participants passed the pen and tablet back to the experimenter. Users tended to hold the device securely, in more of a power grip, and extended it from their body while keeping it level, so that their intent was clear and so that the other person could grab it from the far side.…”
Section: B12 Passing Gripmentioning
confidence: 76%
“…We explored one final interaction, that of passing a tablet to another user as a way to offer an alternative, more physical semantic of sharing content with another user [18], much as observed during device micro-mobility [29,32]. Studies of passing prehension [33] and our observations (B12) indicate a characteristic sequence of motions. A user extends the object to offer it, while holding it level.…”
Section: Detecting Unintentional Thumb Contactmentioning
confidence: 96%